Error Analysis in ESL Writing: A Case Study at Academic English Program at St. Michael's College, VT - Nurwahida (Institut Parahikma Indonesia, 2018)
Analyzing and evaluating linguistic errors in students’ English writings have been an interesting attempt in the field of second or foreign language teaching and learning. Error analysis and evaluation provide a change on direction toward a more positive treatment on student linguistic errors in their writings. It enables language teachers to depict and understand how language learning takes place in the minds of learners. This study seeks about the error analysis made by an ESL student at Academic English Program at St. Michael’s College, VT, USA. The essays and interview were used to take data on student’s grammatical errors and his preferable types of feedback in his writing revision process. The result showed that the negative transfer from mother tongue does have negative influence to student’s ESL writing. In addition, the student prefers direct feedback better than indirect feedback in correcting their errors. Direct feedback is considered more beneficial because he can directly focus on the error and do immediate correction.